2023
DOI: 10.1021/acsestengg.3c00019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Differences in the Response of SARS-CoV-2 Delta and Omicron to Ultraviolet Radiation

Abstract: One method that can help slow the spread of coronaviruses is disinfection with UV light. The Delta and Omicron variants of the COVID-19 virus (SARS-CoV-2) have come to dominate the later stages of the pandemic due to their higher rates of transmission. In this work, it is shown that a 17% higher UV 254 dose is required for the disinfection of Delta and Omicron variants when compared to the ancestral strain of SARS-CoV-2. The UV 254 disinfection rate constants for SARS-CoV-2 and the Delta and Omicron variants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the seasonal trend tended to disappear in 2022, suggesting the emergence of new variants potentially more resistant to environmental conditions (e.g., high temperatures, UV rays). Such an observation is supported by the work of Gibson and colleagues [50], who observed that a 17% higher dose of UV254 is required for the disinfection of Delta and Omicron variants compared to the ancestral strain of SARS-CoV-2. In fact, in our study, the SARS-CoV-2 concentration did not vary much across seasons during 2022, showing a constant trend more similar to endemic situations, thus suggesting a possible transition of SARS-CoV-2 from an epidemic to an endemic situation, at least in the region under study.…”
Section: Discussionmentioning
confidence: 80%
“…However, the seasonal trend tended to disappear in 2022, suggesting the emergence of new variants potentially more resistant to environmental conditions (e.g., high temperatures, UV rays). Such an observation is supported by the work of Gibson and colleagues [50], who observed that a 17% higher dose of UV254 is required for the disinfection of Delta and Omicron variants compared to the ancestral strain of SARS-CoV-2. In fact, in our study, the SARS-CoV-2 concentration did not vary much across seasons during 2022, showing a constant trend more similar to endemic situations, thus suggesting a possible transition of SARS-CoV-2 from an epidemic to an endemic situation, at least in the region under study.…”
Section: Discussionmentioning
confidence: 80%
“…As mentioned before, differences in relative humidity, aerosol size distribution and composition may influence the UV dose received by individual viruses and their inactivation process 28 , 60 , 61 . Furthermore, studies on multiple variants of SARS-CoV-2 have indicated differences in UV sensitivities between variants 62 64 .…”
Section: Resultsmentioning
confidence: 99%